Resistance to Immunotoxins in Cancer Therapy - Verma, Rama Shanker; Bonavida, Benjamin (Resistance to Targeted Anti-Cancer Therapeutics,, 2015)
This volume is a guide to understanding resistance against targeted therapeutic approaches for cancer using immunotoxins. It contains a detailed review of the history and development of targeted therapy. As well, it includes an in-depth description of the molecular and cellular mechanisms involved in cancer resistance and several novel methods to overcome resistance. Each chapter discusses different aspects of resistance and covers all the factors that may contribute to resistance in cancer cells. Finally, this volume highlights the recent findings and advances associated with tackling cancer resistance.